Blended learning in entrepreneurship education: the assessments of the measurement model using SmartPLS / Noraini Nasirun and T. Ramayah - Nasirun, Noraini; T., Ramayah (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Scholars of blended learning are calling for more empirical research in the area of blended learning in entrepreneurship education. Therefore, the aim of this study is to develop a measurement model that involved student interactions, motivation and student engagement on satisfaction in blended learning among entrepreneurship students. This study was underpinned by the Self-Determination Theory (SDT). The respondents of this study are Universiti Teknologi MARA (UiTM) students who enrolled Fundamental of Entrepreneurship (ENT300) and participated in the flipped classroom module. ENT300 is a university subject, hence massive enrollment is expected every semester. Questionnaires were distributed to the respondents 15 minutes before the class ends in Week 14. The measurements for all constructs were adapted from previous scholars and approved by the ethical committee of the university. Data was analyzed using SmartPLS. The results indicated that the measurement model achieves its reliability and validity thus valid for further analysis. This study contributes to the empirical literature of entrepreneurship education and the practices on handling a massive enrollment using blended learning. The conclusions and recommendations for future research are also presented in this study.